PSYCHOLOGICAL CONFLICT OF THE MAIN CHARACTERS IN THE MOVIE VIVARIUM (2020) - Faiz, Khansa (Journal of English Literature and Linguistic Studies, 2025)
This study aims to analyze the psychological conflict experienced by the main characters in the movie "Vivarium" using Kurt Lewin's Field theory and Sigmund Freud's Psychoanalysis theory as supporting theories. This study adopts a qualitative research approach and content analysis methods to explain the psychological conflicts that occur. The research data was obtained through content analysis of the movie "Vivarium" with a focus on the conflicts experienced by the main characters, namely Gemma and Tom. Field Theory by Kurt Lewin is used to find out the kinds of psychological conflict experienced by the main characters in the movie. Meanwhile, Sigmund Freud's Psychoanalysis theory is used to describe the impact of the psychological conflict on the personality change of the main characters. The results reveals that the main characters faces psychological conflict between the desire for freedom and the need for security. The unnatural and monotonous environment exacerbated this conflict, led to significant psychological changes in the characters. The psychological implications of this conflict include changes in values, life goals, and individual identity.